EFEKTIVITAS TEPUNG BUNGA KECOMBRANG (Nicolaila speciosa Horan) SEBAGAI PENGAWET TERHADAP DAYA SUKA ORGANOLEPTIK DAGING BROILER - Okta Suwarna Perdana; Rr. Riyanti; Dian Septinova (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
Kecombrang flower is a plant source of antioxidants that can be used as a natural preservative because they contain bioactive compounds such as polyphenols, alkaloids, flavonoids, steroids, saponins, and essential oils are thought to have potential as antioxidants. This study aims to determine the effect of adding kecombrang flower powder and optimum doses as a preservative on acceptence test of organoleptic (color, smell, flavor, and tenderness) broiler meat.  This research was conducted at the Laboratory of Animal Production Department of Animal Husbandry, Faculty of Agriculture, University of Lampung and meat samples obtained from the Market Joints. Completely randomized design (CRD) is use with four treatments and twenty replications. Treatment in the form of additional kecombrang flower powder with doses of 0%; 2%; 4%; and 6%. The data were analyzed variance at 5% significance level and continued with Least Significant Difference test (LSD).  These results indicate that administration of kecombrang flower powder at doses of 0%; 2%; 4%; and 6% had no significant effect (P> 0.05) to acceptance test of organoleptic (color, smell, flavor, and tenderness). (Keywords: broiler meat, kecombrang flower powder, color, smell, flavor, tenderness).